Competitiveness of alexandergrass or Bengal dayflower with soybean - Dias,A.C.R. (2010)
Weeds compete with field crops mainly for water, light and nutrients, and the degree of competition is affected by the weed density and the intrinsic competitive ability of each plant species in coexistence. The objective of this research was to compare the competitiveness of alexandergrass (Brachiaria plantaginea) or Bengal dayflower (Commelina benghalensis) in coexistence with soybean, cv. M-Soy 8045. A factorial experiment (2 x 5) with two weed species and five competition proportions was carried out in a completely randomized design with four replicates. Proportions were based on a replacement series competition design, always maintaining the total density of four plants per 10 L plastic pots, which corresponded to 60 plants m ². The weed-crop proportions were: 0:4; 1:3; 2:2; 3:1; 4:0; that corresponded to the proportion of 100, 75, 50, 25 and 0% of soybean plants and the opposite for weeds, B. plantaginea or C. benghalensis plants. Leaf area, shoot dry mass of the weeds and soybean and number of soybean trifoliate leaves were evaluated when the soybean reached the phenologic stage of full flowering. B. plantaginea was a better competitor than soybean plants. Otherwise, C. benghalensis revealed a similar competitive ability that of the soybean. In both cases, there were evidences that intraspecific competition was more important.